Entre a razão e os sentidos, a prescrição e a experiência: Friedrich Schiller e as possibilidades de uma educação alimentar estética - Alcântara, Cláudia Sales de (2013)
Aims to propose a food education for children, and its supporting literature book Ziraldo: Nutty Almanac - Juliet in the culinary world. This proposal seeks to escape the paradigm and move towards a prescriptive model "aesthetic", which has theoretical foundation in the philosophy of the German Friedrich Schiller, specifically in his book Letters on the Aesthetic Education of Man, contributing to the insertion of a new proposal for food education under the context of food security and nutrition. The research, based on the thesis that the aesthetic is a pedagogical proposal that contributes to an education food less prescriptive and more significant in the lives of children, was held at the Nursery-School Aunt Leah, with seven children in the 5th grade of elementary school, where through a Culinary Lab, developed what was called Aesthetic Education Food giving opportunity children with awareness support promoted in the preparation of the recipes in the book Almanac Nutty - Juliet in the culinary world, to reflect on aesthetically their food, contributing to the formation of active subjects and they know make healthier decisions in their daily lives. This is a qualitative study, which used the methodology of bricolage, which enabled to use various tools and techniques for collecting and analyzing data, as a case study, interview, observation, questionnaires, field diary, reflective analysis and discourse analysis. In general, it may be said that this thesis is a descriptive investigation, entered in the field of qualitative research, which develops through a case study. On this journey, in search of food education aesthetic, dialogued with several authors, such as Bezerra, Montanari, Ram, Vergueiro, Kincheloe, Berry, and Pêcheux MINAYO so interdisciplinary, researching on different subjects such as culture, food, Philosophy, Semiotics, Arts and Education, showing the complexity of the proposed topic. It was felt that the research provided sensitize the look, the direct contact with the food, the pleasure in time to make and eat, the ability to try new foods, the pleasure of eating with whom you love, respect for others and sense of solidarity, inclusion of playfulness in a field of knowledge marked by prescription, in addition to learning how to repair revenues.